A Study of the HTS Josephson Junction Formed by a Ga Focused Ion Beam. (July 2020) - Hayashi, K; Ueda, T; Ohtani, R; Ariyoshi, S; Tanaka, S
Abstract: High Temperature Superconductor Josephson Junctions (HTS-JJs) are based on artificial grain boundaries. However, the layout of HTS Superconducting QUantum Interference Devices (SQUIDs) on a bi-crystal substrate was restricted. Therefore, we considered to form low noise nano-bridge JJs by Ga Focused Ion Beam (Ga-FIB) irradiation. An 100 nm thick and 4 μm wide YBa2 Cu3 O7- δ (YBCO) micro-channels protected by a 20 nm thick Au protection layer were irradiated by line scans of Ga-FIB (Acceleration voltage: 40 kV, Beam diameter: ∼30 nm) and they were became normal conductivity except for the restricted region. In those nano-bridges, W N = 500 nm and fluence Φ = 2.0×10 15 ions/cm 2 of the nano-bridge was I C = 170 μA and we confirmed Shapiro steps by microwave irradiation of f RF = 2 GHz.